Analisis Perbandingan Kinerja Reksa Dana Saham Konvensional dengan Saham Syariah - Jefry Caisar; Isni Andriana; Kemas M. Husni Thamrin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to explain the comparative analysis between the performance of conventional equity funds and sharia equity funds using the sharpe, treynor, and jensen methods. The population in this study were all registered conventional equity funds and sharia equity funds on the Otoritas Jasa Keuangan (OJK) in 2017 – 2020. Based on the purposive sampling technique, 21 samples of equity funds were obtained as the samples of this study. The analysis technique in this study is comparative hypothesis testing (differential test). The results of this study indicate that there is no significant difference between the performance of conventional equity funds and sharia equity funds throught the sharpe, treynor, and jensen methods.